1993
DOI: 10.1038/362165a0
|View full text |Cite
|
Sign up to set email alerts
|

Myoblasts transferred to the limbs of embryos are committed to specific fibre fates

Abstract: In the limb bud of the 5-day-old avian embryo, when primary muscle fibre formation is beginning and before specific muscles appear, differences in the expression of fast and slow myosin heavy chain genes can be detected among primary fibres of the premuscle masses. Myoblasts that form colonies of fibres of specific types can be isolated from these limb buds. To assess the role of myoblast commitment in specifying fibre types during embryonic development, we cloned myoblasts of specific types from embryonic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 17 publications
0
73
0
Order By: Relevance
“…It is not yet understood how muscle fiber phenotypes develop or are maintained (15,43,53,60). Nevertheless, both developmental cues and extrinsic signals affect muscle fiber type and gene expression (3,14,19,22,46), and genes, including the myosin and troponin families, human aldolase A, and muscle-specific transcription factors, exhibit differential expression in fast and slow muscles (4,11,23,28,36,52,55,57,58,68). The skeletal muscles we examined contain different compositions of fast-twitch glycolytic fibers (expressing MyHC IIb), fast-twitch oxidative-glycolytic fibers (expressing either MyHC IIa or IIx), and slow-twitch oxidative fibers (expressing ␤/slow MyHC) (24,53,60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not yet understood how muscle fiber phenotypes develop or are maintained (15,43,53,60). Nevertheless, both developmental cues and extrinsic signals affect muscle fiber type and gene expression (3,14,19,22,46), and genes, including the myosin and troponin families, human aldolase A, and muscle-specific transcription factors, exhibit differential expression in fast and slow muscles (4,11,23,28,36,52,55,57,58,68). The skeletal muscles we examined contain different compositions of fast-twitch glycolytic fibers (expressing MyHC IIb), fast-twitch oxidative-glycolytic fibers (expressing either MyHC IIa or IIx), and slow-twitch oxidative fibers (expressing ␤/slow MyHC) (24,53,60).…”
Section: Discussionmentioning
confidence: 99%
“…CAT enzyme standards were analyzed in parallel to ensure that activities of diluted extracts were within the linear range of the assay. Counts per minute (cpm) from [acetyl- 14 C]chloramphenicol were converted to microunits of CAT activity, where 1 U of CAT activity is defined as the amount sufficient to acetylate 1 mol of chloramphenicol per min at 37ЊC (61). Samples which exhibited less than twice the CAT assay background counts per minute (40 to 60 cpm) are indicated as 0 U of CAT per mg of protein.…”
Section: Methodsmentioning
confidence: 99%
“…In the embryo, the intrinsic characteristics of fibers dominate and the pattern of fiber types within embryonic muscles is largely unchanged by the removal of neural influences (Butler et al, 1982;Phillips and Bennett, 1984). Myoblasts, like myotubes, are heterogeneous and are committed to form fibers of a particular type (Stockdale, 1992;Dimario et al, 1993) and this had led to the widely held belief that the intrinsic characteristics of fibers are determined by the myoblasts from which they were initially formed.…”
Section: Tgf-p1 and Muscle Fiber-type Pattern Formationmentioning
confidence: 99%
“…To delineate the two, myoblast transplantation experiments have been performed by several laboratories. In chickenquail transplantation experiments, it was shown that the embryonic myoblasts (which form primary myotubes) are committed to a specific fiber type independent of the environment (DiMario et al, 1993;Nikovits et al, 2001). A similar result was obtained by limb bud transplantation experiments showing that myoblasts migrating early (embryonic myoblasts) and late (fetal myoblasts) into limb buds have mainly slow and fast fiber fate, respectively (Van Swearingen and Lance-Jones, 1995).…”
Section: Introductionmentioning
confidence: 99%